2012
DOI: 10.1111/j.1365-2923.2011.04196.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of collaborative interactivity in the observational practice of clinical skills

Abstract: The results suggest that video-based observational practice can be effective in extending simulation-based learning, but its effectiveness is mediated by the amount of time the learner spends engaged in the practice and the type of learning activities the learner performs in the observational practice environment. We speculate that increasing collaborative interactivity supports observational learning by increasing the extent to which the educational environment can accommodate learners' specific needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 28 publications
2
32
0
2
Order By: Relevance
“…This study demonstrates that observational learning in a context that includes errors can advance the development of clinical skills in novices. The results presented here are consistent with recent evidence which supports the use of mixed observational content for both experimentally constrained spatio‐temporal motor tasks and clinical procedural skills . However, our findings indicate that observational learning that includes error demonstrations has this benefit on learning only if the observer is given information that confirms that what he or she has observed is errorful.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This study demonstrates that observational learning in a context that includes errors can advance the development of clinical skills in novices. The results presented here are consistent with recent evidence which supports the use of mixed observational content for both experimentally constrained spatio‐temporal motor tasks and clinical procedural skills . However, our findings indicate that observational learning that includes error demonstrations has this benefit on learning only if the observer is given information that confirms that what he or she has observed is errorful.…”
Section: Discussionsupporting
confidence: 91%
“…The participants watched and assessed one of their group‐specific observational videos each day within a web‐based learning environment over the course of 4 days (see Grierson et al . for a review of the Internet‐mediated observational network).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…58 Feedback can be facilitated through enhanced CBVI activities and collaborative learning environments. 59 Psychological science gave us the theory of deliberate practice. 53 Now, educators are producing research suggesting that success in the work (and home) environment has more to do with "character" (rather than the highest scores) and that these qualities (perseverance, curiosity, conscientiousness, optimism, gratitude, and self-control) can be learned.…”
Section: Future Researchmentioning
confidence: 99%
“…). Similarly, Grierson and colleagues 12 showed that observational learning could be supported through the provision of additional collaborative peer feedback.…”
Section: Introductionmentioning
confidence: 96%